Changing Faces: Factors Associated with the Intention to Pursue Plastic Surgery and Practice in Underserved Areas - Mytien Nguyen, MS; Annette Kaminaka, BA; Nicholas N. Brutus, BA; Luis A. Gonzalez, PhD; Amit Ratanpal, BS; Michael Alperovich, MD, MSc; Donna B. Jeffe, PhD; Ashar Ata, MD; Hyacinth R. C. Mason, PhD; Paris D. Butler, MD, MPH (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Improving the number of plastic and reconstructive surgeons who provide care to patients in underserved communities is critical to achieving health equity. We aimed to identify factors associated with graduating medical students’ intentions to pursue plastic surgery and practice in underserved areas. Methods:. De-identified data for US medical school graduates were obtained from the Association of American Medical Colleges for students who matriculated in academic years 2007–2008 and 2011–2012. Data collected included self-reported demographic and future practice intentions. Multivariate analysis was conducted to determine indicators of students’ interest in plastic surgery, and their intention to practice in underserved areas. Results:. Of the 57,307 graduating US medical students in our cohort who completed the Graduation Questionnaire, 532 (0.9%) reported an intention to pursue plastic surgery. Hispanic [adjusted odds ratio (aOR): 1.45; 95% confidence interval (95% CI), 1.07–1.98] and multiracial (aOR: 1.59; 95% CI, 1.03–2.45) students were more likely to pursue plastic surgery compared with other surgical specialties. Among students interested in plastic surgery, compared with non-Hispanic White students, Black (aOR: 6.15; 95% CI, 1.96–19.26) students were more likely to report intention to practice in underserved areas. Students with community-engagement experiences were more likely to report intention to practice in underserved areas. Conclusions:. Diversity among medical trainees pursuing plastic and reconstructive surgery is critical for maintaining and expanding plastic surgery services rendered in underserved areas. These findings suggest that student demographics and experiences with community-engagement experiences are positive indicators of practicing in underserved communities.